The issue of immigrants in Italy: A rational model of immigration management by Italian municipalities - Marco Baudino (IZA Journal of Development and Migration, 2017)
This paper aims to analyze the increasing issue of overcongestion affecting the immigration hosting facilities of many Italian municipalities, as well as the heterogeneity in immigration regulatory behavior emerging among the latter. Since 2014, the immigration rate in Italy has tripled and the redistribution process of immigrants among municipalities has increased in a sustained manner. Municipalities receive financial subsidies from the central government for hosting immigrants; at the same time, many of them have been experiencing a series of rigidities in the form of complaints by both firms and local residents when having to modify their desired rate of immigrant arrivals. I introduce an intertemporal dynamic framework where a municipal authority rationally maximizes its utility from allowing immigrants to relocate to its jurisdiction, while considering the disutility cost of rigidities and the negative repercussions of having a congestion level of its hosting facilities different from the optimal one. From the model, two major findings emerge. Firstly, the optimal congestion level for a municipality always corresponds to a situation of overcongestion. Secondly, even though the level of rigidities does not affect the steady-state level, it does affect the process of convergence towards it, resulting in either monotonic or oscillating paths of convergence.
Keywords: R23; C61; P25; 330; Immigration; Dynamic optimization